Level of Injection in Spinal Anesthesia: Effect on Sensory Anesthetic Level. Issue 1 (January 1993) - Becker, N.; Christiansen, C.; Callesen, T.; Thage, B.; Bertelsen, F.
Abstract : Background and Objectives: A prospective, randomized study was performed to investigate the influence of the level of injection on sensory anesthesia when bupivacaine 0.5% adjusted to 37.0 C was used. Methods: Three milliliters of plain bupivacaine 0.5% were injected at either the L2-3 interspace or the L4-5 interspace. There were 10 patients in each group. The patients were kept sitting for 2 minutes after injection. Results: No significant difference in maximal level of sensory anesthesia was found ( p = 0.123). Conclusion: These preliminary results indicate that if a higher level of injection is more suitable for anatomic reasons, it can safely be used without the risk of a much higher level of sensory blockade.